Effect of Dynamic Circuit Pressures Monitoring on the Lifespan of Extracorporeal Circuit and the Efficiency of Solute Removal During Continuous Renal Replacement Therapy - Li, Peiyun; Zhang, Ling; Lin, Li; Tang, Xin; Guan, Mingjing; Wei, Tiantian; Chen, Lixin (Frontiers in Medicine, 2021)
Objective: To observe the effects of dynamic pressure monitoring on the lifespan of the extracorporeal circuit and the efficiency of solute removal during continuous renal replacement therapy (CRRT). Materials and Methods: A prospective observational study was performed at the West China Hospital of Sichuan University in the intensive care unit. Analyses of the downloaded pressure data recorded by CRRT machines and the solute removal efficiencies, calculated by 2*Ce/(Cpre+Cpost), where Ce, Cpre and Cpost are the concentrations of the effluent, pre-filter blood, and post-filter blood, respectively, were performed. Samples were collected at 0, 2, 6, 12, 24 h when CVVHDF used after the initiation of CRRT. Measurements in concentrations of creatinine, blood urea nitrogen (BUN) and β2-microglobulin in the plasma and effluent were recorded. Results: Extracorporeal circuits characterized by moderate-severe (M-S) access outflow dysfunction (AOD) events, defined as access outflow pressure less than or equal to -200 mm Hg more than 5mins, had shorter median lifespans with no anticoagulation (32.3 hr vs. 10.90 hr, P=0.001) compared with no moderate-severe AOD events group. The significant outcome also existed in regional citrate anticoagulation (RCA) (72 hr vs. 42.47 hr, P=0.02). Moreover, Cox regression analysis revealed that the lack of moderate-severe AOD events, RCA, or continuous veno-venous hemodiafiltration (CVVHDF) independently prolonged the circuit lifespan. All tested solutes removal efficiencies started to decline at 12h. Furthermore, efficiencies of all solutes removal dropped obviously at 24h when TMP≥ 150mmHg. Conclusion: RCA and CVVHDF predicted a longer circuit lifespan. Moderate-severe AOD events were associated with a shorter circuit lifespan when RCA or no anticoagulation was used. Replacement of extracorporeal circuit can be considered when running time of filter lasted to 24 hours with TMP≥ 150mmHg.